2000
DOI: 10.1086/313913
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to Bordetella pertussis Antigens and Clinical Correlations in Elderly Community Residents

Abstract: A serological study to determine the frequency of Bordetella pertussis infection in 100 adults aged >/=65 years was carried out over a 3-year period. Ten serum samples (collected every 4 months) from each subject were examined for IgA and IgG antibodies to the following B. pertussis antigens: pertussis toxin (PT), filamentous hemagglutinin (FHA), pertactin, and fimbriae-2. A >/=2-fold titer increase in ELISA units from one time period to the next was considered serological evidence of infection. The rate of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 31 publications
4
56
1
1
Order By: Relevance
“…During the last two decades, a number of studies have indicated that B. pertussis infections in adolescents and adults are common (55,200,271,354,390,397,534,550,586,634,665,675,695,739,759,788,828,835). There has also been an increase in the number reported cases of pertussis in adolescents and adults in concert with these studies (112,135,199,232,309,702,710,838).…”
Section: B Pertussismentioning
confidence: 96%
“…During the last two decades, a number of studies have indicated that B. pertussis infections in adolescents and adults are common (55,200,271,354,390,397,534,550,586,634,665,675,695,739,759,788,828,835). There has also been an increase in the number reported cases of pertussis in adolescents and adults in concert with these studies (112,135,199,232,309,702,710,838).…”
Section: B Pertussismentioning
confidence: 96%
“…In 3-µM transwell chambers, 10 5 PMNs were allowed to migrate across endothelial cells toward supernatant from alveolar macrophages (Mf) incubated with B. pertussis or B. pertussis∆PTx. Purified PTx or catalytically inactive PTx (∆PTx) were added to the supernatant as indicated.…”
Section: Figurementioning
confidence: 99%
“…However, recent surveys reveal that a majority of individuals in a vaccinated population are transiently infected with the causative agent, Bordetella pertussis, and that it is widespread and endemic (4)(5)(6)(7)(8). In vaccinated populations, however, the bacterium induces a mild form of the disease that often goes undiagnosed (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of pertussis vaccination in adults during an outbreak has been suggested but has yet to be established. 2,7,8 These three clusters also underline the limitation of detection using specific IgA alone. IgA may persist for some time after the acute infection and may have delayed the identification of the initial case.…”
Section: Discussionmentioning
confidence: 96%
“…Other researchers have found an incidence rate of serologically defined infection of 19.7 per 100 person-years in a group of 100 people aged over 65. 2 Pertussis in adults produces considerable morbidity and, in addition, provides a significant reservoir of infection for children.…”
Section: Discussionmentioning
confidence: 99%